Good response to rituximab in chronic lymphocytic inflammation with pontine perivascular enhancement responsive to steroids presenting as tumor‐like infratentorial lesion. Issue 2 (23rd July 2021) - Marangi, Antonio; Zuliani, Luigi; Vitale, Valerio; Mansour, Mariam; Federle, Lisa; Novello, Mariangela; d'Amore, Emanuele Stefano Giovanni; Stenta, Gianola; Perini, Francesco
Abstract: Background: Chronic lymphocytic inflammation with pontine perivascular enhancement responsive to steroids (CLIPPERS) represents a T cell‐mediated inflammatory disorder typically characterized by multiple punctate gadolinium enhancement mainly involving the pontine region. Atypical onset with tumefactive infratentorial lesions has been rarely described, representing a significant diagnostic and therapeutic challenge. Case presentation: We describe a 58‐year‐old man who presented in November 2017 with left‐sided hemihypesthesia followed by gait imbalance and diplopia. The first magnetic resonance imaging scans showed an enhancing infratentorial tumefactive lesion empirically treated with intravenous steroids. Extensive laboratory work‐up for the most common causes of tumor‐like lesions was negative, whereas cerebral biopsy disclosed an accumulation of macrophages, perivascular T lymphocytes and rare B cells. Six months later a control magnetic resonance imaging showed multiple punctate hyperintensities in T2‐weighted images peppering the pons and upper cervical spinal cord, which were considered highly suggestive of CLIPPERS. After 3 months of oral prednisone, treatment with rituximab was initiated in April 2019, under which the patient's conditions fully stabilized. Conclusions: Tumor‐like onset was found to be an extremely rare variant of CLIPPERS, which expands the spectrum of possible magnetic resonance imaging manifestation, which can be observed during the course of this disease. The efficacy of rituximab in the treatment of CLIPPERS syndrome supports the role of B cells as important regulators of T‐cell activity. Abstract : We describe a unique case of chronic lymphocytic inflammation with pontine perivascular enhancement responsive to steroids first presenting with a tumefactive infratentorial lesion. Long‐term follow up allowed us to observe the evolution toward the typical magnetic resonance imaging pattern of chronic lymphocytic inflammation with pontine perivascular enhancement responsive to steroids. Anti‐CD20 monoclonal antibody rituximab was found to be highly effective in the treatment of this rare disease